Does teaching quality matter for Nordic primary school students’ mathematics confidence and mathematics achievement? A multilevel structural equation analysis of Nordic TIMSS 2019 grade 4 data - Lena Asp; Alli Klapp; Monica Rosén (Large-scale Assessments in Education)
Abstract Background Teaching quality is assumed to be an essential prerequisite for student learning outcomes such as mathematics confidence and mathematics achievement. Notwithstanding its significance, empirical research examining the relations between teaching quality and learning outcomes is still limited, particularly among primary school students. Addressing this gap is important for understanding how to support student learning outcomes. This study aims to examine the relationships between student-perceived teaching quality and student outcomes and differences between classrooms. Methods Utilizing Trends in Mathematics and Science Study (TIMSS) data 2019 from fourth graders in mathematics classrooms in the Nordic countries (Denmark, Finland, Norway, and Sweden), the present study examines the relationships between student-perceived teaching quality (classroom management and instructional clarity) and the two student outcomes mathematics confidence and mathematics achievement in Grade 4 at both student and classroom levels. To identify latent constructs of aspects of teaching quality (classroom management and instructional clarity) and mathematics confidence, multilevel confirmatory factor analysis (MCFA) is used in the modelling process. To capture the hierarchical structure of the data, multilevel structural equation modelling (MSEM) is used as it keeps individual and classroom variation separate when investigating relations between teaching quality, mathematics confidence and mathematics achievement. Results This study shows how student-perceived instructional clarity relates substantially to mathematics confidence at both the student- and the classroom levels in the Nordic countries. Student-perceived classroom management relates, at the student-level, significantly and positively to mathematics achievement in all countries but Denmark. At the classroom-level, classroom management relates positively to classroom mathematics achievement in Sweden and Denmark. The relationships between the student background factors and mathematics achievement were higher at both levels compared to the relationships to mathematics confidence. The findings suggest there are differences between classrooms’ mathematics achievement related to the average SES of the classroom. Conclusions The findings highlight the importance of teachers’ generic pedagogical skills for high-quality teaching. The implications from these findings emphasize the importance of teacher education to ascertain teachers’ ability to manage the classroom well to provide students with the opportunity to learn.